Protonated paramagnetic redox forms of di-o-quinone bridged with p-phenylene-extended TTF: A EPR spectroscopy study - Chalkov, Nikolay O.; Cherkasov, Vladimir K.; Abakumov, Gleb A.; Starikov, Andrey G.; Kuropatov, Viacheslav A. (Beilstein Journal of Organic Chemistry, 2016)
The chemical oxidation and reduction processes of deprotonated, direduced o-quinone-exTTF-o-quinone in protic solvents were studied by EPR spectroscopy. The formation of relatively stable paramagnetic protonated redox forms of the parent triad was very surprising. The character of spin-density distribution in the semiquinone–quinone and semiquinone–catechol redox forms indicates that the p-phenylene-extended tetrathiafulvalene connector provides a quite effective electronic communication channel between dioxolene coordination sites. It was found that the deprotonated, direduced o-quinone-exTTF-o-quinone is capable to reduction of the metal copper in solution. The radical anion species formed in this reaction exists in solution as a solvent-separated ion pair with a copper cation. A character of spin-density distribution in a radical anion species leads to the conclusion that the ligand corresponds to type III of the Robin–Day classification.
Keywords: acceptor–donor–acceptor triad; bridging ligand; EPR spectroscopy; extended tetrathiafulvalene; protonated semiquinone